PENGARUH PERCEIVED ORGANIZATIONAL SUPPORT DAN GAYA KEPEMIMPINAN TRANSFORMASIONAL TERHADAP ORGANIZATIOAL CITIZENSHIP BEHAVIOR DI PLATARAN UBUD HOTEL & SPA - Ni Luh Ketut Sri Sulistyawati; Ida Ayu Sri Mahendra Dewi; Irene Hanna H. Sihombing (JURNAL KEPARIWISATAAN, 2023)
Organizational Citizenship Behavior (OCB) is a behavior which is not tied to any reward system, but can help the organization function effectively and efficiently. OCB can be improved with an emotional approach through Perceived Organizational Support and increase work motivation through Transformational Leadership. This study aims to determine the effect of Perceived Organizational Support and Transformational Leadership on Organizational Citizenship Behavior at Plataran Ubud Hotel & Spa. The sample used was 70 people, taken based on saturated sampling technique. The data analysis technique used is multiple linear analysis, while hypothesis testing uses t test and F test. The results show that, 1) Perceived Organizational Support has a positive and significant effect on OCB; 2) Transformational Leadership Style has a positive and significant effect on OCB; 3) Perceived Organizational Support and Transformational Leadership Style simultaneously influence OCB. The test results of the coefficient of determination show that the influence of Perceived Organizational Support and transformational leadership style on OCB is 55.1%. The implication of the results of this study is that to increase employee OCB, companies must increase perceived organizational support and adjust the leadership style that is applied.